Allostasis as a Conceptual Framework Linking Bipolar Disorder and Addiction - Pettorruso, Mauro; De Risio, Luisa; Di Nicola, Marco; Martinotti, Giovanni; Conte, Gianluigi; Janiri, Luigi (Frontiers in Psychiatry, 2014)
Bipolar disorders and addictions constitute reciprocal risk factors and are best considered under a unitary perspective. The concepts of allostasis and allostatic load may contribute to the understanding of the complex relationships between bipolar disorder and addictive behaviors. Allostasis entails the safeguarding of reward function stability by recruitment of changes in the reward and stress system neurocircuitry and it may help to elucidate neurobiological underpinnings of vulnerability to addiction in bipolar patients. Conceptualizing bipolar disorder as an illness involving the cumulative build-up of allostatic states, we hypothesize a progressive dysregulation of reward circuits clinically expressed as negative affective states (i.e. anhedonia). Such negative affective states may render bipolar disorder patients more vulnerable to drug addiction, fostering a very rapid transition from occasional drug use to addiction, through mechanisms of negative reinforcement. The resulting addictive behavior-related allostatic loads, in turn, may contribute to illness progression. This framework could have a heuristic value to enhance research on pathophysiology and treatment of bipolar disorder and addiction comorbidity.